Mengajar dengan Cerita: Pendekatan Berbasis Narasi dalam Pendidikan Pra-Sekolah yang Menyenangkan dan Ramah Anak - Munafiah, Nida'ul; Nirmala, Ine; Ferianto; Astuti, Ria; Munir, Misbachol (Institut Agama Islam Negeri Madura, 2024)
Pre-school education has a crucial role in forming the basis of children's development. This research aims to explore and describe teaching with stories: a narrative-based approach in a fun and child-friendly pre-school learning process at Nur Faqih Kindergarten, East Karawang. This approach is not only directed at delivering learning material, but also creates a fun and child-friendly learning experience and utilizes the power of stories as a learning tool to increase children's enjoyment, involvement and understanding. Qualitative research methods are used with data collection techniques through observation, interviews and documentation analysis. The research results show that the use of a narrative-based approach in Nur Faqih Kindergarten makes a positive contribution to the development of cognitive, social and emotional skills of pre-school children. Stories integrated into learning not only increase children's interest, but also support language development, creativity and problem solving. This narrative-based approach not only creates a fun learning environment, but also helps children understand moral and ethical values through the stories told. Thus, this research contributes to the development of more innovative and interesting learning strategies at the pre-school level.